2021
DOI: 10.1186/s12911-021-01657-w
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of long-term hospitalisation and all-cause mortality in patients with chronic heart failure on Dutch claims data: a machine learning approach

Abstract: Background Accurately predicting which patients with chronic heart failure (CHF) are particularly vulnerable for adverse outcomes is of crucial importance to support clinical decision making. The goal of the current study was to examine the predictive value on long term heart failure (HF) hospitalisation and all-cause mortality in CHF patients, by exploring and exploiting machine learning (ML) and traditional statistical techniques on a Dutch health insurance claims database. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Following the title and abstract screening process, 292 studies were deemed eligible for full‐text screening. Ultimately, during the final phase of full‐text screening, 65 studies (comprising 88 cohorts) met the inclusion criteria and were included in the subsequent meta‐analysis 10–74 . One additional study was identified through a manual cross‐reference of the included studies, bringing the total to 66 studies 75 (online supplementary Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Following the title and abstract screening process, 292 studies were deemed eligible for full‐text screening. Ultimately, during the final phase of full‐text screening, 65 studies (comprising 88 cohorts) met the inclusion criteria and were included in the subsequent meta‐analysis 10–74 . One additional study was identified through a manual cross‐reference of the included studies, bringing the total to 66 studies 75 (online supplementary Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…When building machine learning models for healthcare applications, algorithms need to be compared to appropriate baselines or standards to ensure the performance of these models is high enough to warrant the cost of deploying and maintaining them [26]. Performance of models is typically evaluated in relation to other outcomes [35], [36], [37], [38], [39], [40] or other prediction models [35], [41], [42], [43], [32], [44], [45]. To this end, we test the models built in this study which predict sudden death and other catastrophic cardiovascular events in two ways.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of insurance claims data for clinical findings steadily grew over the last years (Sawicki et al, 2020 ). Initially descriptive statistical methods were used, recently more advanced statistical and machine learning (ML) approaches have been employed in the clinical research (van der Galiën et al, 2021 ). Furthermore, there is a massive interest in the integration of multiple databases from different insurance providers (Riedel et al, 2018 ; Sabaté et al, 2021 ) or with the clinical data (Jones et al, 2018 ).…”
Section: History Established Principles and Current State Of The Artmentioning
confidence: 99%
“…Depending on the country and type of health insurance, certain insurance populations might not accurately represent the general population of the country regarding social status, sex, and age (Barth et al, 2018 ; van der Galiën et al, 2021 ). Therefore, validation studies have been performed for different HIC datasets.…”
Section: Advantages and Challenges Of Using Health Insurance Claims Datamentioning
confidence: 99%
See 1 more Smart Citation